(untitled) (Journal of Hama University, 2019)
The purpose of this study is to show the impact of using internal auditing for the method of root cause analysis (RCA) in the correctness and objectivity of Audit Communications, considering root cause analysis as a tool of strategic planning. This is by conducting a field study in traditional private banks in Hama governorate, through the design of a questionnaire dealing with the variables of research, and distribution internal auditors working in the banks sample study. The study finds that there is an impact of using internal auditing for the method of root cause analysis in the correctness and objectivity of audit Communications, and thiese results are as follows: 1- There is a very significant impact on the use of root-cause analysis by internal auditing. This effect has emerged in a strong positive- relationship between the root cause analysis method and both the correctness and objectivity of audit Communications. 2- The use of an internal audit of the root cause analysis method will lead to submission of audit communications to reflect facts in a more honest and correct manner. 3- The use of an internal audit of the root-cause analysis method will result in more audit-free communications of errors and distortions more than if this method is not used.